1986
DOI: 10.1099/00221287-132-1-143
|View full text |Cite
|
Sign up to set email alerts
|

Induction of  -Lactamase in Proteus vulgaris

Abstract: Various P-lactam antibiotics, including monocyclic P-lactams, induced the P-lactamase of Proteus vulgaris; when clinical isolates were induced by benzylpenicillin, each strain produced a single 0-lactamase but the activity per milligram dry weight differed from strain to strain. The Plactamases of the P. vulgaris strains were heterogeneous with respect to their isoelectric points, but had almost the same specific activities, substrate specificities and Michaelis constants. The kinetics of P-lactamase formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
(15 reference statements)
2
7
0
Order By: Relevance
“…bacteria are ,-lactamase positive or ,-lactamase negative (1,6). Moreover, it is well known that the ,-lactamase inducibility of bacteria depends markedly on the P-lactam antibiotic used and its concentration in vitro (8,10). In this study, we have shown that this phenomenon could also take place in vivo.…”
Section: Discussionsupporting
confidence: 51%
“…bacteria are ,-lactamase positive or ,-lactamase negative (1,6). Moreover, it is well known that the ,-lactamase inducibility of bacteria depends markedly on the P-lactam antibiotic used and its concentration in vitro (8,10). In this study, we have shown that this phenomenon could also take place in vivo.…”
Section: Discussionsupporting
confidence: 51%
“…The result supports the findings of (Nordstrom & Sykes, 1973;Okonogi, Kuno,& Higashide, 1986;Raimondi, Sisto & Nikaido, 2007) who reported that the specific activity of β-lactamase increased linearly with increasing concentrations of inducer. In addition, Khan, Sallum, Zheng, Nau & Hassan (2014) in their study on rapid determination of β-lactamase and antibiotic activity detected β-lactamase in the absence of inducer however, at a lower level when compared with induction.…”
Section: Discussionsupporting
confidence: 81%
“…Other Proteus vulgaris cephalosporinases have similar substrate profiles but slightly different molecular sizes and isoelectric points: strain TN1945, pI 8.8; molecular mass, 28 kDa; strain GN4413, pI 8.2; molecular mass, 27.5 kDa; strain GN4818, pI 6.9; molecular mass, 27 kDa (212).…”
Section: Discussionmentioning
confidence: 99%